PROUD FLESH SURGICAL MANAGEMENT IN HORSE : A CASE REPORT - Saraswati, Nabila Ayu (VITEK : Bidang Kedokteran Hewan, 2025)
Proud flesh or exuberant granulation tissue is a frequent complication in equine distal limb wounds, often delaying healing. This case report presents a 4-year-old Sandalwood pony mare with proud flesh on the left hindlimb. Diagnostic evaluation, including hematology and histopathology, revealed signs of active inflammation and fibroblast proliferation. Surgical excision and debridement were performed under sedation and local anesthesia to expose healthy tissue in order to support proper healing. Postoperative care included NSAIDs, antibiotics, hemostatic agents, and oral omeprazole to prevent gastric irritation. Daily bandage changes and veterinary monitoring contributed to a satisfactory healing outcome without complications. This case highlights the importance of combined surgical and medical management treatment is effective in treating equine proud flesh.